2022
DOI: 10.21203/rs.3.rs-1610254/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knock down of PCSK9 can improve myocardial ischemia/reperfusion injury by inhibiting autophagy

Abstract: Purpose: To investigate the effect and mechanism of proprotein convertase subtilisin/Kexin type 9 (PCSK9) on myocardial ischemia-reperfusion injury (MIRI) and to provide a reference for clinical prevention and treatment of acute myocardial infarction (AMI).Methods: We established a rat myocardial ischemia/reperfusion (I/R) model and AC16 hypoxia/reoxygenation (H/R) model. A total of 48 adult male Sprague-Dawley rats were randomly assigned into 3 groups (n=16): control(scrambled RNAi was use), ischemia/reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been found that the inhibition of PCSK9 by transfecting cardiomyocytes with siRNA induced an attenuation of LC3-II and beclin-1 expression, which are well-known markers of autophagy in response to ischemia [71]. Analogously, Huang et al [134] demonstrated that PCSK9 knockdown by siRNA reduced myocardial I/R injury via the BNIP-3 mediated autophagic pathway and improved myocardial infarct size and cardiac function. New challenges remain to identify non-coding RNAs that, as reported for other diseases, could have a crucial role even for counteracting I/R.…”
Section: New Preclinical Strategies Against Ischemia/reperfusion Injurymentioning
confidence: 96%
“…It has been found that the inhibition of PCSK9 by transfecting cardiomyocytes with siRNA induced an attenuation of LC3-II and beclin-1 expression, which are well-known markers of autophagy in response to ischemia [71]. Analogously, Huang et al [134] demonstrated that PCSK9 knockdown by siRNA reduced myocardial I/R injury via the BNIP-3 mediated autophagic pathway and improved myocardial infarct size and cardiac function. New challenges remain to identify non-coding RNAs that, as reported for other diseases, could have a crucial role even for counteracting I/R.…”
Section: New Preclinical Strategies Against Ischemia/reperfusion Injurymentioning
confidence: 96%